Paginas infantis (1908), de Presciliana Duarte de Almeida: a obra, a circulação e os valores estéticos - Silva, Ana Paula Serafim Marques da (2023)
In this research, we study the work "Paginas infantis" (1908), which had five editions (1908, 1910, 1914, 1923, and 1934), by the Minas Gerais poet Presciliana Duarte de Almeida (1867-1944). Initially, we delve into the conceptions of children's poetry that circulated in the late 19th and early 20th centuries, based on reading books of that time, anthologies, and publications in newspapers. Next, we investigate Almeida's literary life through data collection, especially from newspapers of the period, emphasizing her participation in the Paulista Academy of Letters. We highlight her involvement in various periodicals, including the founding and supervision of the magazine "A Mensageira" (1897-1900), as well as her contributions to newspapers aimed at women. Additionally, besides publishing poems for children and organizing the anthology "Livro das aves: crestomatia em prosa e verso" (1914), we also examine the poet's works for adult audiences. Finally, the central focus of the research is the study of the various editions of "Paginas infantis" (1908), a publication that includes various texts such as poems, letters, riddles, tales, hymns, verses, and a song. Regarding this work, we observe the thematic diversity of the poems, their formal aspects, the incorporation of oral literature forms, and the illustrations. As a conclusive step, we compile an annotated anthology based on the poems present in our corpus, allowing access to poems that can still engage in a dialogue with contemporary readers. The research is of a documentary and bibliographical nature, with a qualitative and interpretive approach, encompassing the socio-cultural, pedagogical, and literary values propagated during the circulation and reception of the work. As a theoretical basis for understanding the aesthetic effects that poetic language can offer, we study works by Arroyo (2011), Bordini (1991), Camargo (2001), Lajolo (1982), and Lajolo and Zilberman (2007). As a result, we find that "Paginas infantis" (1908), despite being educational material, does not present a repertoire limited only to the dissemination of moral and civic precepts. Instead, it gives preference to artistic content, showcasing important aesthetic values such as rhythm, sonority, onomatopoeias, humor, and dramatic play.